SENTIMENT ANALYSIS OF REVIEW DATA OF THE RUANGGURU ONLINE LEARNING APPLICATION USING THE C5.0 ALGORITHM - Izzah, Nurul; Nur'eni; Pitri, Rizka (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2023)
Sentiment analysis is process to determine the sentiment of a person that is manifested in the form of text. Internet users write their opinions and everything that concerns them in the google play store review column. Moreover, when the world of education could not carry out face-to-face learning due to the covid-19 pandemic, learning turned to e-learning applications. Through this innovation, many pros and cons flow from the community with the existence of Ruangguru online learning application in the world of education. This research was conducted with the aim of determining word cloud visualization and the accuracy of the results of sentiment analysis of review data on the Ruangguru application using the C5.0 algorithm. The word cloud visualization results are dominated by word such as â€œpahamâ€, â€œbagusâ€, â€œmudahâ€, â€œsukaâ€, â€œlanggananâ€, â€œseruâ€, â€œnyamanâ€, â€œsenangâ€, â€œmenarikâ€, â€œkerenâ€, â€œlancarâ€, â€œsuksesâ€. This shows that Ruangguru Application is a good application because it is dominated by positive sentiment words which means that users find it helpful and easy to understand the learning material in Ruangguru. The results of the Confusion Matrix show that the model successfully classifies 0.8557 or 85.57% of the data correctly from all test data